Design of Wireless Network System for Digital Village Using Wireless Distribution System - Muchamad Rusdan (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2019)
The purpose of this research is to create a wireless network design in Cijambe Village using WDS so that Cijambe Village can enjoy internet services through wireless networks, which can be used to find information, communication, and market products owned by village communities. A wireless network is one of the best alternatives in building a computer network that is practical and flexible and has high mobility. Most organizations use wireless networks to support existing cable networks, but in reality, the wireless network still uses Unshielded Twisted Pair (UTP) cable media as the backbone of Access Points (AP). Cijambe Village is a village located in Paseh District, Sumedang Regency. Cijambe village is divided into two hamlets, namely Cijambe Hamlet and Parugpug Hamlet. Cijambe village has an area of 357 hectares. The research method used in this study is a qualitative descriptive research method. The steps taken in this research are analysis and design. the conclusion is that wireless network design for digital villages using Wireless Distribution System (WDS) has a better degree of flexibility than the backbone that uses Unshielded Twisted Pair (UTP) cable. Radio wave signals from 19 AP units can reach the entire area of Cijambe Village which has an area of 357 hectares and is divided into 2 hamlets namely, Hamlet Cijambe and Parugpug Hamlet. The design made has thought of a standard level of security with routers and firewalls.